Everyday hero manifesto - Sharma, Robin (Mumbai Jaico, 2021)
For over twenty-five years, leadership legend and personal-mastery path-blazer Robin Sharma has mentored billionaires, business titans, professional-sports superstars and entertainment royalty via a revolutionary methodology that led them to accomplish rare-air results. Now, in this ground-breaking book, Sharma makes his transformational system available to anyone who is ready for undefeatable positivity, monumental productivity, deep spiritual freedom and a life of helping others. In The Everyday Hero Manifesto you will discover: · The hidden habits used by many of the world s most creative and successful
Keywords: Non-fiction